Composition, negative electrode and battery

By using core-shell structure compositions in the negative electrode material of lithium batteries, and using structural element oxides and modified silicon materials, the problems of structural collapse and insufficient energy density of existing lithium batteries under high current density are solved, and higher capacitance, longer life and better safety are achieved.

CN119560516APending Publication Date: 2025-03-04LARGAN MEDICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411207718.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2024-08-30
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The negative electrode materials of existing lithium batteries, especially carbon or graphite, are prone to structural collapse under high current density, reducing capacity and storage life, and posing safety hazards. At the same time, the energy density of graphite is not enough to meet the needs of large power devices. The silicon-based materials have excessive volume changes during circulation, which affects structural stability.

Method used

The compositions of core-shell structures include core materials and shell materials. The core materials are structural elements oxides, such as niobium-titanium composite oxides, and the shell materials are modified silicon materials. The thin film is formed by modifying the polymer surface to improve the dispersion and coverage of the silicon-based materials to form a stable core-shell structure.

Benefits of technology

This technology can maintain the integrity of the battery structure at high current density, improve charging stability and overall capacity, extend the battery life, and improve the battery safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560516A_ABST
    Figure CN119560516A_ABST
Patent Text Reader

Abstract

The invention provides a composition, a negative electrode and a battery. The composition comprises a core-shell structure, the core-shell structure comprises a core material and a shell material, and the shell material is farther from the center of the core-shell structure than the core material. The core material comprises a structural element oxide, the structural element oxide comprises a structural element, and the structural element is selected from at least two of a group consisting of lithium, titanium, niobium, cobalt, copper, tin, silicon, iron, manganese and nickel. The shell material comprises a mixed material, the mixed material comprises a modified silicon material, and the modified silicon material comprises a silicon-based material and a polymer. When specific conditions are met, the safety, the service life, the stability and the capacitance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composition, a negative electrode and a battery, and in particular to a composition, a negative electrode and a battery capable of improving the safety, service life, stability and capacitance of the battery. Background Art

[0002] Today's batteries are developed with high energy density, high operating voltage, fast charging speed and long cycle life as the research and development goals. Currently, the commonly used negative electrode materials are carbon or graphite. During the cycle process using large currents, the layered carbon or graphite cannot withstand the rapid insertion and migration of ions, which can easily cause irreversible structural collapse and reduce the capacity and storage life. When the current density is too large, polarization is likely to occur, causing lithium ions to be reduced to lithium metal on the surface of the electrode and form lithium dendrites, resulting in internal short circuits in the battery and safety concerns.

[0003] Furthermore, the theoretical energy density of graphite is far lower than the kinetic energy required by large power devices such as electric vehicles, so the introduction of high-energy-density silicon-based materials as new negative electrode materials has become the development trend of subsequent lithium batteries. However, studies have shown that after multiple charge and discharge cycles, batteries with silicon-based materials will experience excessive volume changes due to repeated insertion and removal of lithium ions from the silicon-based materials, which may even cause the material to rupture, seriously affecting the structural stability of the negative electrode and significantly reducing the battery's service life. Summary of the invention

[0004] The present invention selects specific materials to form a core-shell structure, and further manufactures a negative electrode and a battery, which helps the battery adapt to a larger current density and maintain the integrity of the overall structure, and also helps to improve the charging stability and overall capacity of the battery.

[0005] According to the present invention, a composition is provided, comprising a core-shell structure, the core-shell structure comprising a core material and a shell material, the shell material being farther from the center of the core-shell structure than the core material. The core material comprises a structural element oxide, the structural element oxide comprises a structural element, and the structural element is selected from at least two of the group consisting of lithium, titanium, niobium, cobalt, copper, tin, silicon, iron, manganese and nickel. The shell material comprises a mixed material, the mixed material comprises a modified silicon material, and the modified silicon material comprises a silicon-based material and a polymer.

[0006] According to the present invention, a negative electrode is provided, comprising the composition as described in the preceding paragraph.

[0007] According to the present invention, a battery is provided, comprising the negative electrode as described in the preceding paragraph.

[0008] According to the present invention, a composition is provided, comprising a core-shell structure, the core-shell structure comprising a core material and a shell material, the shell material being farther from the center of the core-shell structure than the core material. The core material comprises a structural element oxide, the structural element oxide comprising a niobium-titanium composite oxide. The shell material comprises a mixed material, the mixed material comprising a silicon-based material. The coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: 20.0%≤PCs≤100.0%.

[0009] According to the present invention, a negative electrode is provided, comprising the composition as described in the preceding paragraph.

[0010] According to the present invention, a battery is provided, comprising the negative electrode as described in the preceding paragraph.

[0011] According to the present invention, a composition is provided, comprising a core-shell structure, the core-shell structure comprising a core material and a shell material, the shell material being farther from the center of the core-shell structure than the core material. The core material is selected from at least one of the group consisting of a carbon active material, a structural element mixed oxide, and a tin-based alloy. The shell material comprises a mixed material, the mixed material comprises a modified silicon material, the modified silicon material comprises a silicon-based material and a polymer, and the polymer comprises a siloxane group. The particle size of the core material at D50 is cD50, and the particle size of the silicon-based material at D50 is sD50, which satisfies the following condition: 1.0≤cD50 / sD50≤8000.0. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 A scanning electron microscope image of the surface of a core-shell structure of a battery of a comparative example;

[0013] Figure 2A A scanning electron microscope image of the surface of a core-shell structure of the battery of the first embodiment;

[0014] Figure 2B The surface of the core-shell structure of the first embodiment is 0.02×πR 2 μm 2 Scanning electron microscope image of the area;

[0015] Figure 3 An image diagram showing the element position distribution on the surface of the core-shell structure of the first embodiment; and

[0016] Figure 4 The result of superimposing the scanning electron microscope image and the element position distribution image of the surface of the core-shell structure of the first embodiment. DETAILED DESCRIPTION

[0017] The present invention provides a composition, comprising a core-shell structure, the core-shell structure comprising a core material and a shell material, the shell material being farther from the center of the core-shell structure than the core material. The center may represent the core of the core-shell structure in three-dimensional space.

[0018] The core material comprises a structural element oxide, which comprises a structural element, wherein the structural element is selected from at least two of the group consisting of lithium, titanium, niobium, cobalt, copper, tin, silicon, iron, manganese and nickel; the shell material comprises a mixed material, which comprises a modified silicon material, and the modified silicon material comprises a silicon-based material and a polymer.

[0019] Alternatively, the core material comprises a structural element oxide, which comprises a niobium-titanium composite oxide; the shell material comprises a mixed material, which comprises a silicon-based material.

[0020] Alternatively, the core material is selected from at least one of the group consisting of a carbon active material, a structural element mixed oxide and a tin-based alloy; the shell material comprises a mixed material, the mixed material comprises a modified silicon material, the modified silicon material comprises a silicon-based material and a polymer, and the polymer comprises a siloxane group.

[0021] Thus, the present invention forms a core-shell structure by self-assembling a core material with a relatively large particle size and a shell material with a relatively small particle size through the principle of opposite electrical attraction and heteroaggregation, which not only simplifies the process and increases the overall contact area between the core material and the shell material, but also helps to strengthen the stability of the core-shell structure and improve the energy density. The core material can be a compound formed by at least two of the above structural elements, which can have high conductivity, help to strengthen the performance of the battery's fast charging and effectively reduce the resistance value, and can also have high mechanical stability, help the battery adapt to a larger current density and maintain the integrity of the overall structure, and can also have high heat resistance, which helps to improve the safety and service life of the battery in a high temperature environment. The shell material can include a silicon-based material, and the surface of the silicon-based material can be modified by a polymer, so that the polymer forms an elastic film on the periphery of the silicon-based material, effectively providing a binding effect, and helping to reduce the problem of rupture caused by drastic volume changes of the silicon-based material. The polymer can be charged, which helps to increase the dispersion of silicon-based materials, and more evenly and tightly coat the outer surface of the core material and improve the coverage, avoiding excessive silicon-based materials from agglomerating and causing poor conductivity in the internal area, and is less likely to cause irreversible loss of capacity due to oxidation and reduction. In addition, the core material is selected from carbon active materials, which helps to improve the conductivity of silicon-based materials, and the core material is selected from structural element mixed oxides or tin-based alloys, which helps to improve the stability of battery charging and overall capacity.

[0022] The coverage of silicon-based materials relative to core materials is PCs, which satisfies the following conditions: 20.0% ≤ PCs ≤ 100.0%. By increasing the coverage of silicon-based materials, not only the stress caused by volume expansion due to agglomeration of silicon-based materials is reduced, but also the dispersion of silicon-based materials is increased, and the outer surface of the core material can be more evenly and tightly coated, thereby increasing the contact area between the core material and the silicon-based materials as a whole, which helps to improve the conductivity and energy density. Furthermore, it can meet the following conditions: 40.0% ≤ PCs ≤ 95.0%. Furthermore, it can meet the following conditions: 25.0% ≤ PCs ≤ 98.0%. Furthermore, it can meet the following conditions: 30.0% ≤ PCs ≤ 96.0%. Furthermore, it can meet the following conditions: 35.0% ≤ PCs ≤ 94.0%. Furthermore, it can meet the following conditions: 40.0% ≤ PCs ≤ 92.0%. Furthermore, it can meet the following conditions: 45.0% ≤ PCs ≤ 90.0%.

[0023] The particle size of the core material at D50 is cD50, and the particle size of the silicon-based material at D50 is sD50, which satisfies the following conditions: 1.0≤cD50 / sD50≤8000.0. The particle size of the core material and the particle size of the silicon-based material have an appropriate size ratio, which helps the silicon-based material to be more uniformly and tightly coated on the outer surface of the core material. Furthermore, it can meet the following conditions: 50.0≤cD50 / sD50≤500.0. Furthermore, it can meet the following conditions: 10.0≤cD50 / sD50≤5000.0. Furthermore, it can meet the following conditions: 20.0≤cD50 / sD50≤1000.0. Furthermore, it can meet the following conditions: 30.0≤cD50 / sD50≤800.0. Furthermore, it may satisfy the following condition: 35.0≤cD50 / sD50≤500.0. Furthermore, it may satisfy the following condition: 40.0≤cD50 / sD50≤300.0.

[0024] The particle size of the core material at D50 is cD50, which may satisfy the following conditions: 100.0nm≤cD50≤80000.0nm. By selecting a core material with an appropriate particle size, it helps to reduce the time required for ion conduction and enhance the rate performance. Furthermore, it may satisfy the following conditions: 200.0nm≤cD50≤70000.0nm. Furthermore, it may satisfy the following conditions: 400.0nm≤cD50≤50000.0nm. Furthermore, it may satisfy the following conditions: 600.0nm≤cD50≤40000.0nm. Furthermore, it may satisfy the following conditions: 800.0nm≤cD50≤30000.0nm. Furthermore, it may satisfy the following conditions: 1000.0nm≤cD50≤20000.0nm.

[0025] The particle size of the silicon-based material at D50 is sD50, which can meet the following conditions: 10.0nm≤sD50≤3000.0nm. By selecting a silicon-based material with a smaller particle size, it helps to reduce the stress caused by the volume expansion of the silicon-based material. Furthermore, it can meet the following conditions: 10.0nm≤sD50≤10000.0nm. Furthermore, it can meet the following conditions: 10.0nm≤sD50≤2000.0nm. Furthermore, it can meet the following conditions: 10.0nm≤sD50≤1000.0nm. Furthermore, it can meet the following conditions: 10.0nm≤sD50≤500.0nm. Furthermore, it can meet the following conditions: 20.0nm≤sD50≤400.0nm. Furthermore, it can meet the following conditions: 30.0nm≤sD50≤300.0nm. Furthermore, it may satisfy the following conditions: 40.0 nm ≤ sD50 ≤ 250.0 nm. Furthermore, it may satisfy the following conditions: 50.0 nm ≤ sD50 ≤ 200.0 nm. Furthermore, it may satisfy the following conditions: 60.0 nm ≤ sD50 ≤ 150.0 nm. Furthermore, it may satisfy the following conditions: 70.0 nm ≤ sD50 ≤ 100.0 nm.

[0026] The weight of the core material in the core-shell structure can be greater than the weight of the silicon-based material in the core-shell structure. By having an appropriate weight ratio of the core material and the silicon-based material in the core-shell structure, it is helpful to maintain a balance between the stability of the core-shell structure and the improvement of energy density.

[0027] The structural element oxide may be a niobium-titanium composite oxide. During the lithium insertion process, the niobium-titanium composite oxide has a small crystal volume change and high mechanical stability, so it can adapt to a larger current density and maintain the integrity of the overall structure, avoiding the problem of poor battery cycle life due to structural damage.

[0028] The weight of the niobium-titanium composite oxide relative to the core-shell structure is Wtn, and the weight of the silicon-based material relative to the core-shell structure is Ws, which can meet the following conditions: 10.0≤Wtn / Ws≤500.0. The niobium-titanium composite oxide and the silicon-based material are composed in an appropriate ratio, which helps to improve the charging efficiency and energy density of the battery. Furthermore, it can meet the following conditions: 20.0≤Wtn / Ws≤300.0, thereby helping to enhance the stability of the battery and improve the energy density during high current charging and discharging. Furthermore, it can meet the following conditions: 25.0≤Wtn / Ws≤280.0. Furthermore, it can meet the following conditions: 30.0≤Wtn / Ws≤260.0. Furthermore, it can meet the following conditions: 35.0≤Wtn / Ws≤240.0. Furthermore, it can meet the following conditions: 38.0≤Wtn / Ws≤220.0. Furthermore, it can satisfy the following condition: 40.0≤Wtn / Ws≤210.0.

[0029] The niobium-titanium composite oxide may be a doped niobium-titanium composite oxide. Changing the chemical properties of the niobium-titanium composite oxide by doping helps to reduce the difficulty of electron and ion migration, thereby increasing the conductivity of the niobium-titanium composite oxide.

[0030] The doped niobium-titanium composite oxide may include at least one doping element, and the at least one doping element may be selected from at least one of the group consisting of lithium, manganese, magnesium, iron, copper, cobalt, gallium, tantalum, tungsten, fluorine, phosphorus, sodium and molybdenum. By selecting an element with high conductivity for doping, it is helpful to increase the conductivity of the doped niobium-titanium composite oxide and enhance the fast charging performance of the battery, or by selecting a lighter element for doping, it is helpful to increase the energy density.

[0031] The at least one doping element can be selected from at least one of the group consisting of lithium, manganese, magnesium, iron, copper, fluorine and phosphorus. By doping with the above doping elements, it is helpful to maintain the reversibility of lithium ions embedding and migrating from the niobium titanium composite oxide structure during the redox process, and reduce the increase in resistance after multiple redox cycles.

[0032] The polymer may be polymerized from at least two monomers, and the at least two monomers may include a first monomer and a second monomer. The first monomer may include a siloxane group, and the second monomer may include a carboxyl group or an ester group. The first monomer may be closer to the silicon-based material than the second monomer. The condensation of the first monomer and the silicon-based material to form a stable siloxane structure helps to maintain the integrity of the polymer, and the first monomer and the second monomer contain unsaturated functional groups, and multiple monomers are added and polymerized and copolymerized to form a high molecular polymer, which helps to enhance the protection ability of the high molecular polymer.

[0033] The silicon-based material and the polymer can be covalently bonded. By covalently bonding the outer surface of the silicon-based material to form a polymer protective layer, the polymer has the advantage of elasticity, and can adapt to the drastic volume changes of the silicon-based material during charging and discharging and maintain the integrity of the overall structure.

[0034] The mixed material may further include a carbon-based material. Adding the carbon-based material to the shell material helps to improve the conductivity of the battery.

[0035] The total number of particles of niobium-titanium composite oxide in the core-shell structure is Qtn, and the total number of particles of silicon-based materials in the core-shell structure is Qs, which can meet the following conditions: 0.1≤Log(Qs / Qtn)<10.0. By having an appropriate total number ratio of particles of niobium-titanium composite oxide and silicon-based materials in the core-shell structure, it is helpful to improve the coverage of silicon-based materials and reduce the proportion of silicon-based materials that do not adsorb niobium-titanium composite oxide. Furthermore, it can meet the following conditions: 2.5≤Log(Qs / Qtn)≤7.5. Furthermore, it can meet the following conditions: 0.5≤Log(Qs / Qtn)≤9.0. Furthermore, it can meet the following conditions: 1.0≤Log(Qs / Qtn)≤8.0. Furthermore, it can meet the following conditions: 1.5≤Log(Qs / Qtn)≤7.0. Furthermore, it can meet the following conditions: 2.0≤Log(Qs / Qtn)≤6.0. Furthermore, it may satisfy the following condition: 3.0≤Log(Qs / Qtn)≤6.5. Furthermore, it may satisfy the following condition: 3.2≤Log(Qs / Qtn)≤6.0.

[0036] The particle size of the niobium-titanium composite oxide is Dtn, and the particle size of the silicon-based material at D50 is sD50, which can meet the following conditions: 20.0≤Dtn / sD50≤500.0. The particle size of the niobium-titanium composite oxide and the particle size of the silicon-based material have an appropriate size ratio, which helps to increase the coverage and improve the energy density. Furthermore, it can meet the following conditions: 25.0≤Dtn / sD50≤450.0. Furthermore, it can meet the following conditions: 30.0≤Dtn / sD50≤400.0. Furthermore, it can meet the following conditions: 35.0≤Dtn / sD50≤350.0. Furthermore, it can meet the following conditions: 40.0≤Dtn / sD50≤300.0. Furthermore, it can meet the following conditions: 45.0≤Dtn / sD50≤250.0.

[0037] The present invention further provides a negative electrode, which comprises the aforementioned composition.

[0038] The weight of the core material in the negative electrode is tWc, and the weight of the silicon-based material in the negative electrode is tWs, which can meet the following conditions: 0.1≤tWc / tWs≤100.0. By forming the negative electrode with the core material and the silicon-based material in an appropriate weight ratio, it is helpful to enhance the stability of the battery and improve the energy density during large current charging and discharging. Furthermore, it can meet the following conditions: 0.2≤tWc / tWs≤80.0. Furthermore, it can meet the following conditions: 0.4≤tWc / tWs≤60.0. Furthermore, it can meet the following conditions: 0.6≤tWc / tWs≤50.0. Furthermore, it can meet the following conditions: 0.7≤tWc / tWs≤40.0. Furthermore, it can meet the following conditions: 0.8≤tWc / tWs≤30.0.

[0039] The present invention further provides a battery, which comprises the negative electrode as described above.

[0040] The maximum value of the discharge volume capacity of the battery from the first cycle to the discharge volume capacity of the twentieth cycle is VMax, which can meet the following conditions: 100 mAh / cm 3 ≤VMax≤800mAh / cm 3 Measuring the maximum capacity of the first twenty cycles helps to confirm the capacity of the battery after it reaches a stable state. Furthermore, it can meet the following conditions: 120mAh / cm 3 ≤VMax≤750mAh / cm 3 Furthermore, it can meet the following conditions: 140mAh / cm 3 ≤VMax≤720mAh / cm 3 Furthermore, it can meet the following conditions: 160mAh / cm 3 ≤VMax≤700mAh / cm 3 Furthermore, it can meet the following conditions: 180mAh / cm 3 ≤VMax≤680mAh / cm3. Furthermore, it can meet the following conditions: 200mAh / cm 3 ≤VMax≤650mAh / cm 3 .

[0041] The discharge volume capacity of the battery at the fifth cycle is V5, and the discharge volume capacity of the battery at the tenth cycle is V10, which can meet the following conditions: 0.85≤V10 / V5. By comparing the difference in capacity between the fifth cycle and the short-term cycle number of the battery, it is helpful to judge the durability of the battery. Furthermore, it can meet the following conditions: 0.88≤V10 / V5≤1.30. Furthermore, it can meet the following conditions: 0.90≤V10 / V5≤1.25. Furthermore, it can meet the following conditions: 0.92≤V10 / V5≤1.20. Furthermore, it can meet the following conditions: 0.95≤V10 / V5≤1.15. Furthermore, it can meet the following conditions: 0.98≤V10 / V5≤1.10.

[0042] The discharge volume capacity of the battery at the fifth cycle is V5, and the discharge volume capacity of the battery at the fiftieth cycle is V50, which can meet the following conditions: 0.80≤V50 / V5. By comparing the difference in capacity between the fifth cycle and the mid-term cycle number of the battery, it is helpful to judge the durability of the battery. Furthermore, it can meet the following conditions: 0.85≤V50 / V5≤1.30. Furthermore, it can meet the following conditions: 0.88≤V50 / V5≤1.25. Furthermore, it can meet the following conditions: 0.90≤V50 / V5≤1.20. Furthermore, it can meet the following conditions: 0.92≤V50 / V5≤1.15. Furthermore, it can meet the following conditions: 0.95≤V50 / V5≤1.10.

[0043] The discharge volume capacity of the battery at the fifth cycle is V5, and the discharge volume capacity of the battery at the 100th cycle is V100, which can meet the following conditions: 0.70≤V100 / V5. By comparing the difference in capacity between the fifth cycle of the battery and the long-term cycle number, it is helpful to serve as a basis for judging the battery life. Furthermore, it can meet the following conditions: 0.75≤V100 / V5≤1.35. Furthermore, it can meet the following conditions: 0.80≤V100 / V5≤1.30. Furthermore, it can meet the following conditions: 0.85≤V100 / V5≤1.25. Furthermore, it can meet the following conditions: 0.90≤V100 / V5≤1.20. Furthermore, it can meet the following conditions: 0.95≤V100 / V5≤1.15.

[0044] The total number of times the coulombic efficiency of the battery in the first twenty cycles is greater than 90% and less than 110% is n90E20, which can meet the following conditions: 15≤n90E20≤20. The coulombic efficiency of the previous cycles has reached a high standard, which helps to reduce the impact of lithium loss on the capacity retention rate. Furthermore, it can meet the following conditions: 16≤n90E20≤20. Furthermore, it can meet the following conditions: 17≤n90E20≤20. Furthermore, it can meet the following conditions: 18≤n90E20≤20. Furthermore, it can meet the following conditions: 19≤n90E20≤20. Furthermore, it can meet the following conditions: n90E20=20.

[0045] The composition of the present invention may include a core-shell structure and auxiliary materials.

[0046] The core-shell structure of the present invention may include a core material and a shell material, wherein the main portion of the shell material is farther from the center of the core-shell structure than the core material, or the shell material is located at the periphery of the core material. If the core material particle surface has a pore structure, part of the shell material may also be located in the pore structure on the particle surface. The main portion may be represented by more than 50% of all the shell materials.

[0047] The core material of the present invention may be a structural element oxide, a carbon active material or a tin-based alloy, wherein the structural element oxide may include a structural element composite oxide and a structural element mixed oxide.

[0048] The structural element composite oxide may contain structural elements, and the structural elements may be selected from compounds formed by at least two elements of lithium, titanium, niobium, cobalt, copper, tin, silicon, iron, manganese and nickel, for example: lithium titanium composite oxide, niobium titanium composite oxide, tin-based composite oxide. To further illustrate, the structural element composite oxide may contain compounds formed by at least three of the above structural elements.

[0049] The mixed oxide of structural elements may contain structural elements, and the structural elements may be selected from lithium, titanium, niobium, cobalt, copper, tin, silicon, iron, manganese and nickel. It is further specified that the mixed oxide of structural elements may be a mixture formed by at least two oxides containing the structural elements, for example: a mixture formed by tin oxide and nickel oxide, a mixture formed by tin oxide and titanium oxide, a mixture formed by tin oxide and cobalt oxide, a mixture formed by tin oxide and manganese oxide, a mixture formed by silicon oxide and lithium oxide, a mixture formed by silicon oxide and titanium oxide, a mixture formed by silicon oxide and tin oxide, and a mixture formed by silicon oxide and iron oxide. It is further specified that the mixed oxide of structural elements may be a mixture formed by at least three oxides containing the structural elements.

[0050] The carbon active material of the present invention may be graphite, graphene, carbon microspheres, hard carbon, or soft carbon.

[0051] The shell material of the present invention may be a mixed material, and the mixed material may include a modified silicon material and a carbon-based material, wherein the modified silicon material may include a silicon-based material and an auxiliary material.

[0052] The core-shell structure composition method described in the present invention can add the core material and the shell material to the solution to form a colloidal solution. The core material and the shell material have different electrical properties and can attract each other in the solution, and the core material particle size is larger than the shell material particle size. The shell material can be closely distributed on the periphery of the core material to form a core-shell structure. It is further explained that the electrical properties and the amount of the core material or the shell material can be changed by adjusting the electrolyte added to the solution, the pH value of the solution, etc. The core material can be positively charged and the shell material can be negatively charged and attract each other, or the core material can be negatively charged and the shell material can be positively charged and attract each other. It is further explained that the shell material can use a surface-modified silicon-based material to make it have electrical properties, and attract each other with the core material with different electrical properties, and a layer of carbon-based material can be further covered on the periphery of the core material.

[0053] The coverage rate described in the present invention, wherein the coverage rate of the silicon-based material relative to the core material, is positively correlated with the weight ratio of the core-shell structure precursor added and reaches saturation. When the proportion of silicon-based material added increases, the coverage rate of the surface or pores of the core material covered by the silicon-based material increases, and the thickness of the shell material also increases. The coverage rate can be calculated using the following method: a surface image of the core-shell structure is generated by scanning electron microscopy (SEM) technology, and then an image distribution image of the position distribution of the regional surface elements is obtained by energy dispersive X-ray spectroscopy (EDX) imaging analysis, and the surface image of the core-shell structure and the image distribution image of the position distribution of the regional surface elements are superimposed, and then the color, brightness and shape differences of the superimposed image are analyzed by imaging software (such as ImageJ), and the particle size of the core material is set to R (μm), and at 0.02×πR 2 (μm 2 ) is analyzed within the area of ​​​​the silicon-based material, thereby obtaining the coverage of the silicon-based material relative to the core material. The surface image of the core-shell structure can also be generated by transmission electron microscopy (TEM) technology, and the position distribution image of the regional surface elements can also be obtained by X-ray photoelectron spectroscopy (XPS) imaging analysis. The standards are as follows: the core-shell structure is selected to be independent and complete, and the entire core-shell structure is visible. There are no obvious defects and the shell material is relatively evenly distributed. The area selected for analysis must include the center of the sphere; the single particle size of the core material is calculated as the average of the longest and shortest sides. The particle size and coverage obtained by this method are measured and calculated using two-dimensional images.

[0054] The total number ratio of the shell material to the core material of the present invention is Np. It can be calculated theoretically by assuming that both the core material and the shell material are spheres and the total number of the core material particles is 1, the particle size of the core material is R, the particle size of the shell material is r, the shell material is distributed on the surface of the core material in the densest packing, the surface area of ​​the virtual spherical shell formed by the center of the shell material is A, and the surface area of ​​the equilateral triangle formed by the centers of three adjacent shell materials when the shell material is distributed in the densest packing is a, each equilateral triangle can contribute 0.5 shell materials, and the coverage of the shell material is PC. Its Np can be calculated as follows:

[0055]

[0056] as well as

[0057]

[0058] When R>>r, the calculation method is closer to the actual theoretical value. When the core material is niobium-titanium composite oxide and the shell material is silicon-based material, the total number of particles of niobium-titanium composite oxide in the core-shell structure is Qtn, and the total number of particles of silicon-based material in the core-shell structure is Qs, and Np=Qs / Qtn.

[0059] The niobium-titanium composite oxide described in the present invention may include undoped niobium-titanium composite oxide and doped niobium-titanium composite oxide. The composition of the undoped niobium-titanium composite oxide includes at least niobium element, titanium element and oxygen element. The niobium-titanium composite oxide contains various compounds and can be further represented by the following chemical formula:

[0060] Ti x Nb y O z ;

[0061] where z ≤ 4x + 5y. For example, TiNb2O7, Ti2Nb 10 O 29 、TiNb 14 O 37 and TiNb 24 O 62 . The crystal structure of the niobium-titanium composite oxide can be cubic, monoclinic, orthorhombic, ReO3-type lattice or layered structure, etc. The doped niobium-titanium composite oxide can be selected from at least one compound of the above undoped niobium-titanium composite oxide doped with at least one doping element and can be further represented by the following chemical formula:

[0062] Ti (x-a) Ml a Nb (y-b) M2 b O (z-c) M3 c ;

[0063] where M1, M2 and M3 are doping elements, 0 ≤ a < x, 0 ≤ b < y, 0 ≤ c < z. The structure can be changed by adjusting the doping elements or the doping ratio. At least one auxiliary material can be further selected to coat or fill the surface or pores of the niobium-titanium composite oxide.

[0064] The lithium-titanium composite oxide described in the present invention may include undoped lithium-titanium composite oxide and doped lithium-titanium composite oxide. The composition of the undoped lithium-titanium composite oxide includes at least lithium element, titanium element and oxygen element. The lithium-titanium composite oxide contains various compounds, such as Li4Ti5O 12 , LiTi2O4, Li2Ti3O7 and Li2TiO3. The doped lithium-titanium composite oxide can be selected from at least one compound of the above undoped lithium-titanium composite oxide doped with at least one doping element. The structure can be changed by adjusting the doping elements or the doping ratio. At least one auxiliary material can be further selected to coat or fill the surface or pores of the lithium-titanium composite oxide.

[0065] The doping element of the present invention can be selected from any element of Group IA, Group IIA, Group IVB, Group VB, Group VIB, Group VIIB, Group VIIIB, Group IB, Group IIB, Group IIIA, Group IVA, Group VA, Group VIA, and Group VIIA, and can be further selected from at least one of lithium, boron, fluorine, sodium, magnesium, aluminum, silicon, phosphorus, sulfur, chlorine, calcium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, arsenic, bromine, zirconium, molybdenum, antimony, iodine, tantalum, tungsten, and bismuth. Selecting an element with high conductivity or a relatively light element for doping helps to increase the conductivity of the doped niobium-titanium composite oxide, enhance the fast charging performance of the battery, and improve the energy density.

[0066] The tin-based composite oxide described in the present invention may include tin-nickel composite oxide, tin-iron composite oxide, tin-copper composite oxide, tin-titanium composite oxide, tin-niobium composite oxide, tin-cobalt composite oxide, tin-silicon composite oxide, tin-manganese composite oxide, and tin-lithium composite oxide.

[0067] The tin-based alloy described in the present invention may include tin-phosphorus alloy, tin-sulfur alloy, tin-antimony alloy, tin-cobalt-sulfur alloy, tin-antimony-sulfur alloy, and tin-copper-phosphorus alloy.

[0068] The modified silicon material described in the present invention may include silicon-based materials and auxiliary materials, wherein the silicon-based materials may form a mixture with the auxiliary materials, the silicon-based materials may also form a chemical bond with the auxiliary materials, and the silicon-based materials may also form a film structure with the auxiliary materials. Further explanation, the auxiliary material may be selected from polymers, and the polymer may form a film structure on the periphery of the silicon-based material by chemical bonding or physical mixing, wherein the polymer is polymerized by at least two monomers, and the at least two monomers may include a first monomer and a second monomer, the first monomer includes a siloxane group, and the second monomer includes a carboxyl group or an ester group. The first monomer is closer to the silicon-based material than the second monomer, and the first monomer may contain an unsaturated alkenyl group or an acrylate group and the second monomer contains an unsaturated alkenyl group or an unsaturated acrylate group. The polymer is formed by covalent bonds. A crosslinking agent may be further added to the polymer so that the straight-chain polymers are bonded and crosslinked to form a network structure.

[0069] The silicon-based material of the present invention may be silicon, silicon oxide, silicon-carbon composite, or silicon alloy. The particle size of the silicon-based material at D50 is sD50, and sD50 may be 20 nm, 50 nm, 80 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 800 nm, 1000 nm, 1500 nm, 2000 nm, 2500 nm, or 3000 nm.

[0070] The first monomer of the present invention may contain at least one alkenyl group (-C=C-), carbonyl group (-C=O), carboxyl group (-COOH), amide group (-CONH2) or silyl enol ether (-C=O). Siloxy compounds of ether may include: Ethenyl(trimethoxy)silane, Ethenyl(triethoxy)silane, Ethenyl-dimethoxy-methylsilane, 2-(Chloromethyl)prop-2-enyl-trimethoxysilane, [2-Hydroxy-3-[3-[methyl-bis(trimethylsilyloxy)silyl]propoxy]propyl]2-methylprop-2-enoate, 3-[Dimethyl(trimethyls 1-[3-(trimethoxysilyl)propyl]urea, hydroxyl-terminated vinyl (siloxane and polysiloxane) (vinylmethylsiloxane-dimethylsiloxane silanol terminated copolymer). The siloxy compound may further be, for example, the following structure, but is not limited thereto:

[0071] (R)3-Si-(CH2) n -X-(CH2) m-A;

[0072] Wherein, R is selected from the group consisting of methoxy, ethoxy and siloxy, X is methyl or oxy, A is selected from the group consisting of vinyl, acrylate and methacrylate, and n and m satisfy the following condition: 0≤n+m≤10. The siloxy compound may include: triethoxysilylmethyl 2-methylprop-2-enoate, 2-trimethylsilyloxyethyl 2-methylprop-2-enoate, 3-trimethoxysilylpropyl 2-methylprop-2-enoate (MPS), 4-trimethoxysilylbutyl2-methylprop-2-enoate, 5-trimethoxysilylpentyl 2-methylprop-2-enoate, 6-trimethoxysilylhexyltrimethoxysilane (MPS), 6-trimethoxysilylhexyltrimethoxysilane (MPS), 6-trimethoxysilylbutyl2-methylprop-2-enoate, 6-trimethoxysilylpentyl ...hexyltrimethoxysilane (MPS 2-methylprop-2-enoate), 7-Trimethoxysilylheptyl2-methylprop-2-enoate, 8-Trimethoxysilyloctyl 2-methylprop-2-enoate, 9-Trimethoxysilylnonyl 2-methylprop-2-enoate, 10-Trimethoxysilyldecyl 2-methylprop-2-enoate, Tris(trimethylsilyloxy)silylmethyl2-methylprop-2-enoate, 3-Tris(trimethylsilyloxy)silylpropyl 2-methylprop-2-enoate. Silane alkoxy compounds can form active silanol groups (Si-OH) through hydrolysis reaction, and undergo condensation reaction with silicon-based materials (especially silicon oxide formed on the surface by oxidizing agents) to form siloxane compounds (Siloxane) with a silicon-oxygen-silicon (Si-O-Si) structure.The above-mentioned oxidant can oxidize the silicon-hydrogen bonds (Si-H) on the surface of the silicon-based material into silanol groups (Si-OH), or oxidize silicon into silicon dioxide, which helps to form an oxide layer on the surface of the silicon-based material.

[0073] The second monomer of the present invention may include a carboxyl group or an ester group, such as 2-(Dimethylamino)ethyl 2-methylprop-2-enoate (DMAEMA), methyl methacrylate (Methyl2-methylprop-2-enoate; MMA), methyl acrylate (Methylprop-2-enoate; MA), 2-ethylhexyl prop-2-enoate (2EHA), acrylic acid (Prop-2-enoic acid; AA), isobutyl methacrylate (2-methylpropyl2-methylprop-2-enoate; IBMA), benzyl methacrylate (Benzyl2-methylprop-2-enoate; BZMA), tetrahydrofurfuryl acrylate (Oxolan-2-ylmethylprop-2-enoate; THFA), 2-(2-Ethoxyethoxy)ethylprop-2-enoate (EDGA), dodecyl methacrylate (Dodecyl prop-2-enoate; LA) or a combination of the above monomers.

[0074] The crosslinking agent of the present invention can make the straight-chain polymers mutually bonded and crosslinked to form a network structure. The crosslinking agent can be any terminally ethylenically unsaturated compound, which can include: ethylenediaminetetraacetic acid (2,2′,2″,2″-(Ethane-1,2-diyldinitrilo)tetraacetic acid; EDTA), ethoxylated-9Trimethylolpropane Triacrylate; TMP9EOTA, ethylene glycol dimethacrylate (2-(2-methylprop-2-enoyloxy)ethyl2-methylprop-2-enoate), diethylene glycol dimethacrylate (2-[2-(2-methylprop-2-enoyloxy)ethoxy]ethyl 2-methylprop-2-enoate), triethylene glycol dimethacrylate (2-[2-[2-(2-methylprop-2-enoyloxy)ethoxy]ethoxy]ethyl2-methylprop-2-enoate), tetraethylene glycol dimethacrylate (2-[2-[2-[2-(2-methylprop-2-enoyloxy)ethoxy]ethoxy]ethyl2-methylprop-2-enoate), allyl methacrylate (prop-2-enyl2-methylprop-2-enoate), 1,3-propylene glycol dimethacrylate (3-(2-methylprop-2-enoyloxy)propyl 2-methylprop-2-enoate), 2,3-propylene glycol dimethacrylate ([2-methyl-3-(2-methylprop-2-enoyloxy)propyl]2-methylprop-2-enoate), 1,4-butanediol dimethacrylate (4-(2-methylprop-2-enoyloxy)butyl 2-methylprop-2-enoate), 1,6-hexanediol dimethacrylate (6-(2-methylprop-2-enoyloxy)hexyl 2-methylprop-2-enoate).

[0075] The silicon-carbon composite of the present invention may include a membrane structure of silicon-coated carbon shell, a silicon-carbon yolk-shell structure, and a porous structure. The membrane structure of silicon-coated carbon shell is formed by anaerobic high-temperature pyrolysis to coat the carbon shell on the periphery of the silicon material; the silicon-carbon yolk-shell structure is formed by generating silicon oxide on the silicon surface, coating the periphery of the silicon material with a layer of carbon shell by anaerobic high-temperature pyrolysis, and then removing silicon oxide by hydrofluoric acid (HF) to break the silicon particles into fine nanoparticles; the porous structure is formed by carbonizing the intermediate product to form a silicon carbide ceramic porous material through a low self-diffusion coefficient of the material or adding a foaming material, and sintering or electrochemical corrosion.

[0076] The carbon-based material of the present invention can be formed by carbonizing a carbon-containing precursor through heat treatment, wherein the carbon-containing precursor may include an organic compound, wherein the organic compound may further include sugars, asphalts or organic polymers.

[0077] The carbon conductive material described in the present invention can be graphite, carbon microspheres, carbon fibers, hard carbon, soft carbon, conductive graphite (KS6, SFG6), graphene, acetylene black, Ketjen black, carbon black (Carbon black, Super P), and carbon nanotubes (Carbon Nanotube; CNT).

[0078] The auxiliary material described in the present invention may include polymers, metals, alloys, non-metallic oxides, metal oxides, fluorides, organic compounds, adhesives, conductive agents or additives.

[0079] The niobium-titanium composite oxide described in the present invention is represented by TNO, methacryloylpropyltrimethoxysilane is represented by MPS, dimethylaminoethyl acrylate is represented by DMAEMA, acrylic acid is represented by AA, methyl methacrylate is represented by MMA, methyl acrylate is represented by MA, and isooctyl acrylate is represented by 2EHA. All relevant configurations of the core material and the shell material in the composition described in the present invention can be further prepared into a core-shell structure, an electrode piece, and a battery charge and discharge test according to relevant proportions. The present invention only shows some relevant configurations, and tables with no data or unable to be calculated are marked with "-".

[0080] The adhesive of the present invention may be polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), polyethylene (PE), polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polypropylene (PP), polyacrylonitrile (PAN), carboxymethyl cellulose (CMC), polytetrafluoroethylene (PTFE), ethylene propylene monomer (EPDM), chlorosulfonated polyethylene (CSM), or alginic acid obtained by linear polymerization of monouronic acid.

[0081] The conductive agent described in the present invention can be graphite, conductive graphite (KS6, SFG6), graphene, acetylene black, Ketjen black, carbon black (Carbon black, Super P), carbon nanotube (Carbon Nanotube; CNT), carbon microspheres, carbon fibers, hard carbon, soft carbon, aluminum powder (Aluminum), nickel powder (Nickel), titanium dioxide (Titanium dioxide), potassium titanate fiber (Potassiumhexatitanate; PHT) or a combination thereof.

[0082] The additives described in the present invention may be carbonate compounds, lactides, ether-containing cyclic compounds, aromatic compounds, phosphorus-containing compounds, boron-containing compounds, inorganic oxides or combinations thereof. Adding an appropriate amount of the additives helps to improve the performance of the battery, for example: improving the SEI film composition, improving high temperature and high voltage performance, improving ion conductivity, reducing electrolyte impedance, improving cycle stability, stabilizing the integrity of positive and negative electrode materials, and increasing electrochemical stability.

[0083] The negative electrode material of the present invention may include a core-shell structure, an auxiliary material, a lithium-containing metal compound, a lithium-containing metal oxide, metallic lithium or a combination thereof.

[0084] The metal salts described in the present invention may be inorganic acid lithium salts containing LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiC4BO8, LiTFSI, LiFSI, LiNO3, LiGaCl4, etc.; fluorine-containing lithium sulfonate salts such as LiCF3SO3, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiC(CF3SO2)3; LiBF2(C2O4)(LiDFOB), LiB(C2O4)2(LiBOB) or combinations thereof. The above metal salts may contain a variety of different oxidation states.

[0085] The positive electrode material described in the present invention may be a lithium composite metal oxide containing lithium or at least one metal, such as lithium iron phosphate (LiFePO4), lithium manganese oxide (LiMnO2, LiMn2O4), lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium nickel cobalt oxide (LiNiCoO2), lithium nickel manganese oxide (LiNiMnO4), lithium manganese cobalt oxide (LiCoMnO2, LiCoMnO4), lithium nickel manganese cobalt oxide (LiNiCoMnO2, LiNiCoMnO4) or a combination of the above. The above-mentioned lithium composite metal oxide may contain a variety of different oxidation states.

[0086] The electrolyte of the present invention may be composed of metal salts, additives and organic solvents, wherein the proportion of the organic solvent is greater than that of the additives, and the electrolyte state may be liquid, colloidal or solid. The additives and organic solvents used as electrolytes may be physically mixed, and at least one of the following additives or organic solvent monomers may be selected as a polymerization precursor.

[0087] The organic solvent described in the present invention can be carbonate, carboxylic acid ester, ether, sulfide or a combination thereof, wherein the organic solvent described can also be used as an additive.

[0088] The organic solvent of the present invention has a polymerizable olefin group in its structure and can be used as a monomer of the second structure precursor, such as: vinylene carbonate (2H-1,3-Dioxol-2-one; Vinylene carbonate; VC), vinylethylene carbonate (4-Vinyl-1,3-dioxolan-2-one; Vinylethylene carbonate; VEC), vinylene trithiocarbonate (1,3-Dithiole-2-thione; Vinylene trithiocarbonate), cyclobutene sulfone (2,5-Dihydrothiophene-1,1-dioxide), divinyl sulfone (1-ethenylsulfonylethene), propenyl-1,3-sultone (Prop-1-ene-1,3-sultone), ether-containing cyclic compound additives or aromatic compound additives.

[0089] The carbonate organic solvent (carbonate ester) of the present invention can be a compound in which the hydrogen atoms of the hydroxyl groups in the carbonic acid molecule are partially or completely replaced by alkyl groups, and can be divided into cyclic carbonates and linear carbonates, wherein the linear carbonates can include: dimethyl carbonate (dimethyl carbonate; DMC), diethyl carbonate (diethyl carbonate; DEC), dipropyl carbonate (dipropyl carbonate; DPC), ethyl methyl carbonate (ethyl methyl carbonate; EMC), methyl propyl carbonate (methyl propyl carbonate; MPC), ethyl propyl carbonate (ethyl propylcarbonate; EPC), 2,2,2-trifluoroethyl methyl carbonate (methyl2,2,2-trifluoroethyl carbonate; FEMC).The cyclic carbonates may include: ethylene carbonate (1,3-Dioxolan-2-one; Ethylene carbonate; EC), propylene carbonate (4-Methyl-1,3-dioxolan-2-one; Propylene carbonate; PC), trimethylene carbonate (1,3-Dioxan-2-one; Trimethylene carbonate; TMC), 1,2-butylene carbonate (4-Ethyl-1,3-dioxolan-2-one; 1,2-Butylene carbonate), 2,3-butylene carbonate ((4R,5S)-4,5-Dimethyl-1,3-dioxolan-2-one; cis-2,3-Butylene carbonate), 1,2-pentylene carbonate (1,2-Pentylene carbonate), 2,3-pentylene carbonate (2,3-Pentylene carbonate), vinylene carbonate (2H-1,3-Dioxol-2-one; Vinylene carbonate), 1,2-pentylene carbonate (1,2-Pentylene carbonate), 2,3-pentylene carbonate (2,3-Pentylene carbonate), 2H-1,3-Dioxol-2-one; Vinylene carbonate, 2H-1,3-Dioxol-2-one; Vinylene carbonate, 2H-1,3-Dioxol-2-one; Vinylene carbonate, 2H-1,3-Dioxol-2-one; Vinylene carbonate, 2H-2,3-Dioxol-2-one; carbonate; VC), vinyl ethylene carbonate (4-Vinyl-1,3-dioxolan-2-one; Vinylethylene carbonate; VEC), fluoroethylene carbonate (4-Fluoro-1,3-dioxolan-2-one; Fluoroethylene carbonate; FEC), difluoroethylene carbonate (trans-4,5-Difluoro-1,3-dioxolan-2-one; Difluoroethylene carbonate; DFEC), trithioethylene carbonate (1,3-Dithiole-2-thione; Vinylene trithiocarbonate) or a combination thereof.

[0090] The carboxylic acid ester organic solvent of the present invention is prepared by esterification reaction of alcohol and carboxylic acid, and can be methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, lactone or a combination thereof, wherein lactone can be further described as comprising a 1-oxacycloalkan-2-one structure, which refers to a compound containing a hydroxyl group and a carboxylic acid, and the intramolecular condensation forms a cyclic carboxylic acid ester monomer, and there can be a variety of combinations according to the position of the hydroxyl group in the ring and the number of carbon atoms in the ring, and can include: α-acetolactone (Oxiran-2-one; α-acetolactone), β-propiolactone (Oxetan-2-one; β-propiolactone e), γ-butyrolactone (Oxolan-2-one; γ-butyrolactone), γ-valerolactone (5-Methyloxolan-2-one; γ-valerolactone), σ-valerolactone (Oxan-2-one; σ-valerolactone), γ-caprolactone (5-Ethyloxolan-2-one; γ-caprolactone), ε-caprolactone (Oxepan-2-one; ε-caprolactone), 6-gluconolactone (D-Glucono-1,5-lactone; δ-gluconolactone) or a combination thereof.

[0091] The ether organic solvent of the present invention can be tetrahydrofuran (Oxolane; THF), 2-methyltetrahydrofuran (2-Methyloxolane; 2-MeTHF), 1,3-dioxolane (1,3-Dioxolane; DOL), 4-methyl-1,3-dioxolane (4-Methyl-1,3-dioxolane; 4-MeDOL), dimethoxymethane (Dimethoxymethane; DMM), 1,2-dimethoxyethane (1,2-Dimethoxyethane; DME), 2,2-dimethoxypropane (2,2-Dimethoxypropane; DMP), 1,2-bis(2-cyanoethoxy)ethane (1,2-Bis(2-cyanoethoxy)ethane; DENE), diethylene glycol dimethyl ether (1-Methoxy-2-(2-methoxyethoxy)ethane; DG) or a combination thereof.

[0092] The sulfide-containing organic solvent of the present invention can be divided into sulfonyl compounds (sulfone group; -(O=)S(=O)-), sulfonate compounds (sulfonate group; -SO2O -), wherein the sulfonyl compounds may include: cyclobutene sulfone (2,5-Dihydrothiophene-1,1-dioxide), divinyl sulfone (1-ethenylsulfonylethene); wherein the sulfonate compounds may be further divided into mesylate (Mesylate; CH3SO2O - ), trifluoromethanesulfonate (Trifluoromethanesulfonate; CF3SO2O - ), p-toluenesulfonyl group (Tosyl), may include ethyl methanesulfonate (1-Methylsulfonyloxyethane), methyl p-toluenesulfonate (Methyl4-methylbenzenesulfonate), 1,3-propanesultone (Oxathiolane 2,2-dione), propenyl-1,3-sultone (Prop-1-ene-1,3-sultone), 1,3-propylene glycol cyclic sulfate (1,3,2-Dioxathiane2,2-Dioxide) or a combination thereof.

[0093] The lactone cyclic ester described in the present invention may be a polycyclic diester monomer formed by esterification condensation of two identical or different compounds both containing hydroxy acid, and may include: glycolide (1,4-Dioxane-2,5-dione; glycolide), lactide (3,6-Dimethyl-1,4-dioxane-2,5-dione; lactide) or a combination thereof, wherein, according to the stereoisomers formed by the difference in the spatial arrangement of atoms, lactide can be further divided into LL-lactide ((R,R)-3,6-Dimethyl-1,4-dioxane-2,5-dione; LL-lactide), DD-lactide ((S,S)-3,6-Dimethyl-1,4-dioxane-2,5-dione; DD-lactide), and DL-lactide ((meso)-3,6-Dimethyl-1,4-dioxane-2,5-dione; DL-lactide). Alternatively, carboxylic acid compounds containing hydroxyl groups can be directly copolymerized to form polymers without going through a ring-opening reaction, and may include: 2-hydroxyacetic acid (2-Hydroxyacetic acid; glycolic acid), 3-hydroxypropanoic acid (3-Hydroxypropanoic acid; lactic acid), 4-hydroxybutanoic acid (4-Hydroxybutanoic acid), 5-hydroxyvaleric acid (5-Hydroxyvaleric acid) or a combination thereof.

[0094] The ether-containing cyclic compound additive of the present invention may be a crown ether, wherein the crown ether is a ethyleneoxy group (-CH2CH2O-) as the main repeating unit structure, and may include: 9-crown-3 (1,4,7-Trioxonane; 9-Crown-3), 12-crown-4 (1,4,7,10-Tetraoxacyclododecane; 12-Crown-4), 15-crown-5 (1,4,7,10,13-Pentaoxacyclopentadecane; 15-Crown-5), 18-crown-6 (1,4,7,10,13,16-Hexaoxacyclooctadecane; 18-Crown-6), 21-crown- Ether-7 (1,4,7,10,13,16,19-Heptaoxacycloheneicosane; 21-Crown-7), dibenzo-18-crown-6 (6,7,9,10,17,18,20,21-Octahydrodibenzo[b,k][1,4,7,10,13,16]hexaoxacyclooctadecine; Dibenzo-18-crown-6), diaza-18-crown-6 (1,4,10,13-tetraoxa-7,16-diazacyclooctadecane; Diaza-18-crown-6) or a combination thereof.

[0095] The aromatic compound additive of the present invention may include: methoxybenzene, 1-ethynyl-4-methoxybenzene, tert-butylbenzene, fluorobenzene, 1,2-difluorobenzene, 1,1′-oxydibenzene, 1,4-diphenylbenzene, 2-fluoro-4-(2-methyl-2-propanyl)aniline, N-phenyl-3-aminopropyltrimethoxysilane (N-[3-(Trimethoxysilyl)propyl]aniline) or a combination thereof.

[0096] The phosphorus-containing compound additive of the present invention can be tris(trimethylsilyl)phosphite (TMSPi), tris(2,2,2-trifluoroethyl)phosphite (Tris(2,2,2-trifluoroethyl)phosphite), triphenyl phosphite (Triphenyl phosphite), ethoxy(pentafluoro)cyclotriphosphazene (1,3,5,2,4,6-triazatriphosphorine, 2-ethoxy-2,4,4,6,6-pentafluoro-2,2,4,4,6,6-hexahydro-) or a combination thereof.

[0097] The boron compound additive of the present invention can be trimethyl borate, tris(trimethylsilyl) borate, 2,4,6-trimethyl-1,3,5,2,4,6-trioxatriborinane or a combination thereof.

[0098] The inorganic oxide additive of the present invention may be a composite material such as lithium lanthanum zirconium oxide (LiLaZrO), lithium lanthanum zirconium tantalum oxide (LiLaZrTaO), lithium lanthanum titanium oxide (LiLaTiO), lithium phosphate (LiPO), lithium fluorinated phosphate (LiPOF), lithium titanium phosphate (LiTiPO), lithium aluminum germanium phosphate (LiAlGeP), lithium aluminum titanium phosphate (LiAlTiPO), lithium germanium phosphorus sulfur oxide (LiGePSO), lithium tin phosphorus sulfur oxide (LiSnPSO), lead zirconium titanium oxide (PbZrTiO), lead lanthanum zirconium titanium oxide (PbLaZrTiO), barium titanium oxide (BaTiO), etc. The above-mentioned inorganic oxide additive may contain a variety of different oxidation states, or Al2O3, TiO2, SiO2, SnO2, NiO, ZnO, CaO, MgO, ZrO2, CeO2, Y2O3, etc., which can reduce the crystallinity of the polymer electrolyte, thereby increasing the ionic conductivity and the physical and mechanical strength of the electrolyte, and helping to enhance the battery cycle life.

[0099] The isolation membrane described in the present invention can be a film with a porous structure, which can contain a single-layer or multi-layer film of polyolefin, polyamide, or polyester fiber, such as polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), acrylonitrile-butadiene-styrene copolymer (ABS), or epoxy resin; or it can contain at least one inorganic ceramic composite film such as Mg(OH)2, MgO, BaSO4, SnO2, NiO, CaO, A1203, ZnO, SiO2, TiO2, or a combination thereof on the surface, and the above-mentioned inorganic ceramic composite film can contain a variety of different oxidation states.

[0100] The negative electrode weight percentage described in the present invention does not include the weight of the collector.

[0101] The battery cycle number described in the present invention is defined as the state of the battery being a commercially available product. The first test in this state is regarded as the first cycle defined in the present invention, and the completion of one discharge and one charge test is regarded as one cycle number, and the cycle number is accumulated accordingly.

[0102] The capacitance described in the present invention can measure the charging capacitance and the discharging capacitance of a battery. The capacitance can be calculated by volume capacitance (mAh / cm3) and weight capacitance (mAh / g). The volume capacitance indicates the capacitance that can be provided by each cubic centimeter of an electrode in a battery. When calculating the volume capacitance, the volume of the collector must be deducted. The weight capacitance indicates the capacitance that can be provided by each gram of an electrode in a battery. When calculating the weight capacitance, the weight of the collector must be deducted. The electrode can be a positive electrode or a negative electrode.

[0103] The current collector of the present invention can be a metal foil or a substrate made of a conductive polymer, wherein the metal foil can be selected from aluminum, copper, titanium, nickel, tantalum, stainless steel or alloys thereof.

[0104] The C-rate (C) described in the present invention may represent the current magnitude when a battery is fully discharged in one hour, and C may be used as a unit of current for charging and discharging a battery.

[0105] The battery measurement voltage range described in the present invention can select a more suitable voltage range according to the redox potential of the positive and negative electrode materials. The voltage range can be selected from 0V-5.0V, preferably 0V-3.0V, preferably 1.0V-4.5V, and preferably 2.5V-4.5V.

[0106] The discharge volumetric capacity described in the present invention can be expressed as CiVj, and the discharge weight capacity described can be expressed as CiGj, wherein i represents the current in C for charging and discharging, and j represents the number of cycles of charging and discharging of the battery.

[0107] The total number of times the coulombic efficiency described in the present invention meets a certain percentage range can be expressed as nxCyEz, where x represents the lower limit of this specific percentage range, y represents the current in C for charging and discharging, and z represents the cut-off cycle number of battery charging and discharging.

[0108] The average value of the coulombic efficiency described in the present invention can be expressed as aCyEz, wherein y represents the current used for charging and discharging in units of C, and z represents the number of charge and discharge cutoff cycles of the battery.

[0109] The particle size of the present invention can be determined by dynamic light scattering to measure the amplitude of light scattered by particles in Brownian motion over time to determine the particle size and its particle size distribution. The particle size can be obtained according to the Stokes-Einstein equation, which is as follows:

[0110] D = kT / (3πηDf);

[0111] Where D is the particle size (unit: m), k is the Boltzmann constant (unit: J / K), T is the absolute temperature (unit: K), and n is the solvent viscosity (unit: kgxm -1 ×s -1 ), Df is the diffusion coefficient (unit: m 2 ×s -1 ).

[0112] The particle size distribution described in the present invention indicates the distribution of particle sizes of various sizes in the object to be tested. According to the proportion of each particle size distribution and the cumulative percentage based on volume, a cumulative particle size distribution function can be obtained. For example, when the particle size with a cumulative particle size distribution percentage of 50% is defined as D50, it can be said that 50% of the particles in the object to be tested have a particle size smaller than D50, and the same applies to D10 and D90. If there is no special explanation, D50 is used as the standard for judging the particle size.

[0113] The core particle size of the present invention can be determined by analyzing the diffraction peak {111} of silicon grains using an X-ray diffractometer, according to the Scherrer formula:

[0114] L = (k × λ) / (β cos (θ / 2));

[0115] Wherein, L is the diameter of silicon grains (in nm), k is the shape factor (about 0.9, but varies with the actual shape of the crystal), β is the half-height width of the diffraction peak {111} (in radians), and θ is the position of the diffraction peak {111}.

[0116] The negative electrode plate of the present invention can be manufactured by single-layer or double-layer coating, vacuum coating or composite structure.

[0117] The roughness described in the present invention is the arithmetic mean height of the surface according to the surface property parameter Sa (μm) of ISO 251781. The area of ​​the region for measuring the roughness is set to be at least greater than 10000 μm2. The height of the average surface is the arithmetic mean of the heights of the coordinates Z (x, y) of each point in the region. Sa is the average value of the absolute value of the height difference of the coordinates Z (x, y) of each point in the region relative to the average surface. According to the following formula:

[0118]

[0119] Where A is the area of ​​the region (μm2) and h is the height of the average surface (μm).

[0120] The conductivity of the present invention adopts the electrochemical impedance spectroscopy (EIS) method, which applies an alternating current of 1 Hz to 100 Hz with an amplitude of 50 mV to the polymer or electrolyte, measures the resistance value, and then calculates the conductivity using the following formula:

[0121] Ci = (1 / R) × (L / A);

[0122] Where Ci(S×cm -1 ) is the conductivity, R (Ω) is the resistance, L (cm) is the distance between the two electrodes, A (cm 2 ) is the cross-sectional area of ​​the object to be tested and the electrode, (L / A) can be expressed as the conductivity coefficient (cm -1 ).

[0123] The electrochemical stability of the present invention is measured by linear sweep voltammetry (LSV) at a scan rate of 0.1 V / s at Li / Li + By measuring the relative voltage between -5V and 5V, the corresponding change in the relationship between current and potential can be obtained.

[0124] The battery assembly described in the present invention may include a battery shell, a spring, a weight, a cover plate, a pole ear, and a cap.

[0125] The bipolar battery described in the present invention may include a bipolar battery electrode sheet and an electrolyte. One side of the bipolar battery electrode sheet is a positive electrode, which includes a positive electrode material, and the other side is a negative electrode, which includes a negative electrode material. Two bipolar battery electrodes are connected by an electrolyte (the electrolyte contacts the positive electrode of one bipolar battery electrode sheet and the negative electrode of the other bipolar battery electrode sheet) to form a bipolar battery unit. Multiple bipolar battery units are connected in series to form a bipolar battery.

[0126] The battery described in the present invention can be a primary battery or a secondary battery. The electrochemical carrier of the primary battery or the secondary battery can be at least one of a button-type carrier, a winding carrier or a stacked carrier. It can be applied to portable electronic products such as digital cameras, mobile phones, laptop computers, game console handles, etc. that require lightweight and thin designs, and can also be applied to large-scale power storage industries such as light electric vehicles and electric vehicles.

[0127] According to the above implementation mode, specific examples are proposed below and described in detail with experimental data.

[0128] <Comparative Example>

[0129] Please refer to Figure 1 , Figure 1 The comparative example is a scanning electron microscope image of a core-shell structure surface of a battery. The comparative example is a battery, wherein the negative electrode comprises a composition, wherein the composition comprises a core-shell structure, wherein the core-shell structure comprises a core material and a shell material, wherein the shell material is further away from the center of the core-shell structure than the core material.

[0130] In the battery of the comparative example, the core material comprises a structural element oxide, the structural element oxide comprises a niobium-titanium composite oxide, the particle size of the core material at D50 is cD50, and the particle size of the niobium-titanium composite oxide is Dtn, which satisfies the following conditions: cD50 = 9278.1 nm; and Dtn = 6345.6 nm.

[0131] In the battery of the comparative example, the shell material comprises a silicon-based material. The particle size of the silicon-based material at D50 is sD50, and the coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: sD50=80.0 nm; and PCs=0%.

[0132] In the battery of the comparative example, the particle size of the niobium-titanium composite oxide is Dtn, and the particle size of the silicon-based material at D50 is sD50, which satisfies the following condition: Dtn / sD50=79.3.

[0133] In the battery of the comparative example, the weight of the core material in the negative electrode is tWc, and the weight of the silicon-based material in the negative electrode is tWs, which satisfies the following conditions: tWc=1.00; tWs=0.05; and tWc / tWs=20.0.

[0134] The detailed data of the battery of the comparative example are listed in Table 1 below.

[0135] <First Embodiment>

[0136] Please refer to Figure 2A , Figure 2B , Figure 3 and Figure 4 , Figure 2AThis is a scanning electron microscope image of the surface of a core-shell structure of the battery of the first embodiment. Figure 2B The surface of the core-shell structure of the first embodiment is 0.02×πR 2 μm 2 Scanning electron microscope image of the area Figure 3 This is an image diagram of the element position distribution on the surface of the core-shell structure of the first embodiment. Figure 4 The first embodiment is a battery, wherein the negative electrode comprises a composition, wherein the composition comprises a core-shell structure, wherein the core-shell structure comprises a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0137] In the battery of the first embodiment, the core material comprises a structural element oxide, the structural element oxide comprises a niobium-titanium composite oxide, the particle size of the core material at D50 is cD50, and the particle size of the niobium-titanium composite oxide is Dtn, which satisfies the following conditions: cD50=9278.1nm; and Dtn=6957.3nm.

[0138] In the battery of the first embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, the modified silicon material includes a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, and the coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: sD50 = 80.0 nm; and PCs = 27.0%.

[0139] In the battery of the first embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacrylpropyltrimethoxysilane, and the second monomer is dimethylaminoethyl acrylate.

[0140] In the battery of the first embodiment, the particle size of the core material at D50 is cD50, and the particle size of the silicon-based material at D50 is sD50, which satisfies the following condition: cD50 / sD50=116.0.

[0141] In the battery of the first embodiment, the particle size of the niobium-titanium composite oxide is Dtn, and the particle size of the silicon-based material at D50 is sD50, which satisfies the following condition: Dtn / sD50=87.0.

[0142] In the battery of the first embodiment, the total number of particles of the niobium-titanium composite oxide in the core-shell structure is Qtn, and the total number of particles of the silicon-based material in the core-shell structure is Qs, which satisfies the following condition: Log (Qs / Qtn) = 3.9.

[0143] In the battery of the first embodiment, the weight of the niobium-titanium composite oxide relative to the core-shell structure is Wtn, and the weight of the silicon-based material relative to the core-shell structure is Ws, which satisfies the following condition: Wtn / Ws=148.7.

[0144] In the battery of the first embodiment, the weight of the core material in the negative electrode is tWc, and the weight of the silicon-based material in the negative electrode is tWs, which satisfies the following conditions: tWc=9.00; tWs=1.00; and tWc / tWs=9.0.

[0145] The detailed data of the battery of the first embodiment are listed in Table 1 below.

[0146] <Second Embodiment>

[0147] The second embodiment is a battery, wherein the negative electrode of the battery comprises a composition, wherein the composition comprises a core-shell structure, wherein the core-shell structure comprises a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0148] In the battery of the second embodiment, the core material comprises a structural element oxide, the structural element oxide comprises a niobium-titanium composite oxide, the particle size of the core material at D50 is cD50, and the particle size of the niobium-titanium composite oxide is Dtn, which satisfies the following conditions: cD50=9278.1nm; and Dtn=7958.7nm.

[0149] In the battery of the second embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, the modified silicon material includes a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, and the coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: sD50 = 80.0 nm; and PCs = 50.7%.

[0150] In the battery of the second embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacrylpropyltrimethoxysilane, and the second monomer is dimethylaminoethyl acrylate.

[0151] The detailed data of the battery of the second embodiment are listed in the following Table 1. The other parameter definitions of the second embodiment in Table 1 are the same as those of the first embodiment and are not repeated here.

[0152]

[0153]

[0154] <Third Embodiment>

[0155] The third embodiment is a battery, wherein the negative electrode of the battery comprises a composition, wherein the composition comprises a core-shell structure, wherein the core-shell structure comprises a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0156] In the battery of the third embodiment, the core material comprises a structural element oxide, the structural element oxide comprises a niobium-titanium composite oxide, the particle size of the core material at D50 is cD50, and the particle size of the niobium-titanium composite oxide is Dtn, which satisfies the following conditions: cD50=13085*2nm; and Dtn=15688.6nm.

[0157] In the battery of the third embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, the modified silicon material includes a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, and the coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: sD50 = 80.0 nm; and PCs = 86.8%.

[0158] In the battery of the third embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacrylpropyltrimethoxysilane, and the second monomer is dimethylaminoethyl acrylate.

[0159] The detailed data of the battery of the third embodiment are listed in the following Table 2. The other parameter definitions of the third embodiment in Table 2 are the same as those of the first embodiment and are not repeated here.

[0160] <Fourth Embodiment>

[0161] The fourth embodiment is a battery, wherein the negative electrode includes a composition, wherein the composition includes a core-shell structure, wherein the core-shell structure includes a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0162] In the battery of the fourth embodiment, the core material comprises a structural element oxide, the structural element oxide comprises a niobium-titanium composite oxide, the particle size of the core material at D50 is cD50, and the particle size of the niobium-titanium composite oxide is Dtn, which satisfies the following conditions: cD50=16011.6nm; and Dtn=13490.2nm.

[0163] In the battery of the fourth embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, the modified silicon material includes a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, and the coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: sD50 = 80.0 nm; and PCs = 81.1%.

[0164] In the battery of the fourth embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacrylpropyltrimethoxysilane, and the second monomer is dimethylaminoethyl acrylate.

[0165] Detailed data of the battery of the fourth embodiment are listed in the following Table 2. The other parameter definitions of the fourth embodiment in Table 2 are the same as those of the first embodiment and are not repeated here.

[0166] <Fifth Embodiment>

[0167] The fifth embodiment is a battery, wherein the negative electrode includes a composition, wherein the composition includes a core-shell structure, wherein the core-shell structure includes a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0168] In the battery of the fifth embodiment, the core material comprises a structural element oxide, the structural element oxide comprises a niobium-titanium composite oxide, the particle size of the core material at D50 is cD50, and the particle size of the niobium-titanium composite oxide is Dtn, which satisfies the following conditions: cD50=10749.6nm; and Dtn=18914.9nm.

[0169] In the battery of the fifth embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, the modified silicon material includes a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, and the coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: sD50 = 80.0 nm; and PCs = 58.2%.

[0170] In the battery of the fifth embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacrylpropyltrimethoxysilane, and the second monomer is dimethylaminoethyl acrylate.

[0171] Detailed data of the battery of the fifth embodiment are listed in the following Table 2. The other parameter definitions of the fifth embodiment in Table 2 are the same as those of the first embodiment and are not repeated here.

[0172]

[0173]

[0174]

[0175] <Sixth Embodiment>

[0176] The sixth embodiment is a battery, wherein the negative electrode includes a composition, wherein the composition includes a core-shell structure, wherein the core-shell structure includes a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0177] In the battery of the sixth embodiment, the core material comprises a structural element oxide, the structural element oxide comprises a niobium-titanium composite oxide, the particle size of the core material at D50 is cD50, and the particle size of the niobium-titanium composite oxide is Dtn, which satisfies the following conditions: cD50=13704.9nm; and Dtn=17703.4nm.

[0178] In the battery of the sixth embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, the modified silicon material includes a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, and the coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: sD50 = 80.0 nm; and PCs = 68.6%.

[0179] In the battery of the sixth embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacrylpropyltrimethoxysilane, and the second monomer is dimethylaminoethyl acrylate.

[0180] Detailed data of the battery of the sixth embodiment are listed in the following Table 3. The other parameter definitions of the sixth embodiment in Table 3 are the same as those of the first embodiment and are not repeated here.

[0181] <Seventh Embodiment>

[0182] The seventh embodiment is a battery, wherein the negative electrode includes a composition, wherein the composition includes a core-shell structure, wherein the core-shell structure includes a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0183] In the battery of the seventh embodiment, the core material comprises a structural element oxide, the structural element oxide comprises a niobium-titanium composite oxide, the particle size of the core material at D50 is cD50, and the particle size of the niobium-titanium composite oxide is Dtn, which satisfies the following conditions: cD50=12546.6nm; and Dtn=5080.8nm.

[0184] In the battery of the seventh embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, the modified silicon material includes a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, and the coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: sD50 = 80.0 nm; and PCs = 64.4%.

[0185] In the battery of the seventh embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacrylpropyltrimethoxysilane, and the second monomer is dimethylaminoethyl acrylate.

[0186] Detailed data of the battery of the seventh embodiment are listed in the following Table 3. The other parameter definitions of the seventh embodiment in Table 3 are the same as those of the first embodiment and are not repeated here.

[0187] <Eighth Embodiment>

[0188] The eighth embodiment is a battery, wherein the negative electrode includes a composition, wherein the composition includes a core-shell structure, wherein the core-shell structure includes a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0189] In the battery of the eighth embodiment, the core material comprises a structural element oxide, the structural element oxide comprises a niobium-titanium composite oxide, the particle size of the core material at D50 is cD50, and the particle size of the niobium-titanium composite oxide is Dtn, which satisfies the following conditions: cD50=9952.2nm; and Dtn=6834.9nm.

[0190] In the battery of the eighth embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, the modified silicon material includes a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, and the coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: sD50 = 80.0 nm; and PCs = 66.3%.

[0191] In the battery of the eighth embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacrylpropyltrimethoxysilane, and the second monomer is dimethylaminoethyl acrylate.

[0192] Detailed data of the battery of the eighth embodiment are listed in the following Table 3. The other parameter definitions of the eighth embodiment in Table 3 are the same as those of the first embodiment and are not repeated here.

[0193]

[0194]

[0195]

[0196] <Ninth Embodiment>

[0197] The ninth embodiment is a battery, wherein the negative electrode includes a composition, wherein the composition includes a core-shell structure, wherein the core-shell structure includes a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0198] In the battery of the ninth embodiment, the core material comprises a structural element oxide, the structural element oxide comprises a niobium-titanium composite oxide, the particle size of the core material at D50 is cD50, and the particle size of the niobium-titanium composite oxide is Dtn, which satisfies the following conditions: cD50=4099.1nm; and Dtn=4107.2nm.

[0199] In the battery of the ninth embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, the modified silicon material includes a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, and the coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: sD50 = 80.0 nm; and PCs = 41.2%.

[0200] In the battery of the ninth embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacrylpropyltrimethoxysilane, and the second monomer is dimethylaminoethyl acrylate.

[0201] Detailed data of the battery of the ninth embodiment are listed in the following Table 4. The other parameter definitions of the ninth embodiment in Table 4 are the same as those of the first embodiment and are not repeated here.

[0202] <Tenth Embodiment>

[0203] The tenth embodiment is a battery, wherein the negative electrode includes a composition, wherein the composition includes a core-shell structure, wherein the core-shell structure includes a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0204] In the battery of the tenth embodiment, the core material comprises a structural element oxide, and the structural element oxide comprises a niobium-titanium composite oxide. The particle size of the core material at D50 is cD50, which satisfies the following condition: cD50=14935.3 nm.

[0205] In the battery of the tenth embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, the modified silicon material includes a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, and the coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: sD50 = 80.0 nm; and PCs = 32.0%.

[0206] In the battery of the tenth embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacrylpropyltrimethoxysilane, and the second monomer is dimethylaminoethyl acrylate.

[0207] Detailed data of the battery of the tenth embodiment are listed in the following Table 4. The other parameter definitions of the tenth embodiment in Table 4 are the same as those of the first embodiment and are not repeated here.

[0208] <Eleventh Embodiment>

[0209] The eleventh embodiment is a battery, wherein the negative electrode includes a composition, wherein the composition includes a core-shell structure, wherein the core-shell structure includes a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0210] In the battery of the eleventh embodiment, the core material comprises a structural element oxide, and the structural element oxide comprises a lithium-titanium composite oxide. The particle size of the core material at D50 is cD50, which satisfies the following condition: cD50=28439.3 nm.

[0211] In the battery of the eleventh embodiment, the shell material comprises a mixed material, the mixed material comprises a modified silicon material, the modified silicon material comprises a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, which satisfies the following condition: sD50=80.0 nm.

[0212] In the battery of the eleventh embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacrylpropyltrimethoxysilane, and the second monomer is acrylic acid.

[0213] The detailed data of the battery of the eleventh embodiment are listed in the following Table 4. The other parameter definitions of the eleventh embodiment in Table 4 are the same as those of the first embodiment and are not repeated here.

[0214]

[0215]

[0216]

[0217] <Twelfth Embodiment>

[0218] The twelfth embodiment is a battery, wherein the negative electrode comprises a composition, wherein the composition comprises a core-shell structure, wherein the core-shell structure comprises a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0219] In the battery of the twelfth embodiment, the core material comprises a structural element oxide, and the structural element oxide comprises a structural element composite oxide. The particle size of the core material at D50 is cD50, which satisfies the following condition: cD50=595.6 nm.

[0220] In the battery of the twelfth embodiment, the shell material comprises a mixed material, the mixed material comprises a modified silicon material, the modified silicon material comprises a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, which satisfies the following condition: sD50=80.0 nm.

[0221] In the battery of the twelfth embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacrylpropyltrimethoxysilane, and the second monomer is methyl methacrylate.

[0222] Detailed data of the battery of the twelfth embodiment are listed in the following Table 5. The other parameter definitions of the twelfth embodiment in Table 5 are the same as those of the first embodiment and are not repeated here.

[0223] <Thirteenth Embodiment>

[0224] The thirteenth embodiment is a battery, wherein the negative electrode includes a composition, wherein the composition includes a core-shell structure, wherein the core-shell structure includes a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0225] In the battery of the thirteenth embodiment, the core material comprises a structural element oxide, and the structural element oxide comprises a structural element composite oxide. The particle size of the core material at D50 is cD50, which satisfies the following condition: cD50=606.6 nm.

[0226] In the battery of the thirteenth embodiment, the shell material comprises a mixed material, the mixed material comprises a modified silicon material, the modified silicon material comprises a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, which satisfies the following condition: sD50=80.0 nm.

[0227] In the battery of the thirteenth embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacrylpropyltrimethoxysilane, and the second monomer is methyl acrylate.

[0228] Detailed data of the battery of the thirteenth embodiment are listed in the following Table 5. The other parameter definitions of the thirteenth embodiment in Table 5 are the same as those of the first embodiment and are not repeated here.

[0229] <Fourteenth Embodiment>

[0230] The fourteenth embodiment is a battery, wherein the negative electrode includes a composition, wherein the composition includes a core-shell structure, wherein the core-shell structure includes a core material and a shell material, wherein the shell material is farther from the center of the core-shell structure than the core material.

[0231] In the battery of the fourteenth embodiment, the core material comprises a carbon active material, and the carbon active material comprises graphite. The particle size of the core material at D50 is cD50, which satisfies the following condition: cD50=13290.0 nm.

[0232] In the battery of the fourteenth embodiment, the shell material comprises a mixed material, the mixed material comprises a modified silicon material, the modified silicon material comprises a silicon-based material and a polymer. The particle size of the silicon-based material at D50 is sD50, which satisfies the following condition: sD50=80.0 nm.

[0233] In the battery of the fourteenth embodiment, the polymer is polymerized by at least two monomers, the at least two monomers include a first monomer and a second monomer, the first monomer is methacryloylpropyltrimethoxysilane, and the second monomer is isooctyl acrylate.

[0234] Detailed data of the battery of the fourteenth embodiment are listed in the following Table 5. The other parameter definitions of the fourteenth embodiment in Table 5 are the same as those of the first embodiment and are not repeated here.

[0235]

[0236]

[0237]

[0238] Although the present invention has been disclosed as above in the form of an implementation method, it is not intended to limit the present invention. Anyone skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be determined by the scope defined by the attached claims.

Claims

1. A composition, characterized in that Include: A core-shell structure, comprising a core material and a shell material, wherein the shell material is farther away from the center of the core-shell structure than the core material; wherein the core material comprises a structural element oxide, the structural element oxide comprises a structural element, and the structural element is selected from at least two of the group consisting of lithium, titanium, niobium, cobalt, copper, tin, silicon, iron, manganese and nickel; The shell material includes a mixed material, the mixed material includes a modified silicon material, and the modified silicon material includes a silicon-based material and a polymer.

2. The composition according to claim 1, characterized in that The particle size of the core material at D50 is cD50, which satisfies the following conditions: 100.0nm≤cD50≤80000.0nm.

3. The composition according to claim 1, characterized in that The particle size of the silicon-based material at D50 is sD50, which satisfies the following conditions: 10.0nm≤sD50≤3000.0nm.

4. The composition according to claim 1, characterized in that The particle size of the core material at D50 is cD50, and the particle size of the silicon-based material at D50 is sD50, which satisfies the following conditions: 1.0≤cD50 / sD50≤8000.

0.

5. The composition according to claim 4, characterized in that The weight of the core material in the core-shell structure is greater than the weight of the silicon-based material in the core-shell structure.

6. The composition according to claim 1, wherein The structural element oxide is a niobium-titanium composite oxide.

7. The composition according to claim 6, characterized in that The weight of the niobium-titanium composite oxide relative to the core-shell structure is Wtn, and the weight of the silicon-based material relative to the core-shell structure is Ws, which satisfies the following conditions: 10.0≤Wtn / Ws≤500.

0.

8. The composition according to claim 6, characterized in that The niobium-titanium composite oxide is a doped niobium-titanium composite oxide.

9. The composition according to claim 8, characterized in that The doped niobium-titanium composite oxide contains at least one doping element, and the at least one doping element is selected from at least one of the group consisting of lithium, manganese, magnesium, iron, copper, cobalt, gallium, tantalum, tungsten, fluorine, phosphorus, sodium and molybdenum.

10. The composition according to claim 9, characterized in that The at least one doping element is selected from at least one of the group consisting of lithium, manganese, magnesium, iron, copper, fluorine and phosphorus.

11. The composition according to claim 1, wherein The polymer is polymerized from at least two monomers, wherein the at least two monomers include a first monomer and a second monomer; Wherein, the first monomer comprises a siloxane group, and the second monomer comprises a carboxyl group or an ester group; The first monomer is closer to the silicon-based material than the second monomer.

12. The composition according to claim 11, characterized in that The silicon-based material is covalently bonded to the polymer.

13. The composition according to claim 1, wherein The mixed material also contains a carbon-based material.

14. A negative electrode, characterized in that: Include: The composition according to claim 1.

15. The negative electrode according to claim 14, characterized in that The weight of the core material in the negative electrode is tWc, and the weight of the silicon-based material in the negative electrode is tWs, which meets the following conditions: 0.1≤tWc / tWs≤100.

0.

16. A battery, characterized in that: Include: The negative electrode as claimed in claim 14.

17. The battery according to claim 16, characterized in that The maximum value of the discharge volumetric capacity of the battery from the first cycle to the discharge volumetric capacity of the twentieth cycle is VMax, which satisfies the following conditions: 100 mAh / cm 3 ≤VMax≤800mmAh / cm 3 。 18. The battery according to claim 16, characterized in that The discharge volume capacity of the battery at the fifth cycle is V5, and the discharge volume capacity of the battery at the tenth cycle is V10, which meets the following conditions: 0.85≤V10 / V5.

19. The battery according to claim 16, characterized in that The discharge volume capacity of the battery at the fifth cycle is V5, and the discharge volume capacity of the battery at the fiftieth cycle is V50, which meets the following conditions: 0.80≤V50 / V5.

20. The battery according to claim 16, characterized in that The discharge volume capacity of the battery at the fifth cycle is V5, and the discharge volume capacity of the battery at the 100th cycle is V100, which meets the following conditions: 0.70≤V100 / V5.

21. The battery according to claim 16, characterized in that The total number of times that the coulombic efficiency of the battery in the first twenty cycles is greater than 90% and less than 110% is n90E20, which satisfies the following conditions: 15≤n90E20≤20.

22. A composition, characterized in that Include: A core-shell structure, comprising a core material and a shell material, wherein the shell material is farther away from the center of the core-shell structure than the core material; Wherein, the core material comprises a structural element oxide, and the structural element oxide comprises a niobium-titanium composite oxide; Wherein, the shell material comprises a mixed material, and the mixed material comprises a silicon-based material; The coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: 20.0%≤PCs≤100.0%.

23. The composition according to claim 22, characterized in that The total number of particles of the niobium-titanium composite oxide in the core-shell structure is Qtn, and the total number of particles of the silicon-based material in the core-shell structure is Qs, which satisfies the following conditions: 0.1≤Log(Qs / Qtn)<10.

0.

24. The composition according to claim 23, characterized in that The coverage of the silicon-based material relative to the core material is PCs, which satisfies the following conditions: 40.0%≤PCs≤95.0%.

25. The composition according to claim 24, characterized in that The total number of particles of the niobium-titanium composite oxide in the core-shell structure is Qtn, and the total number of particles of the silicon-based material in the core-shell structure is Qs, which satisfies the following conditions: 2.5≤Log(Qs / Qtn)≤7.

5.

26. The composition according to claim 22, characterized in that The particle size of the niobium-titanium composite oxide is Dtn, and the particle size of the silicon-based material at D50 is sD50, which satisfies the following conditions: 20.0≤Dtn / sD50≤500.

0.

27. The composition according to claim 22, wherein The niobium-titanium composite oxide is a doped niobium-titanium composite oxide.

28. The composition according to claim 27, characterized in that The doped niobium-titanium composite oxide includes at least one doping element, and the at least one doping element is selected from at least one of the group consisting of lithium, manganese, magnesium, iron, copper, fluorine and phosphorus.

29. The composition according to claim 28, characterized in that The weight of the niobium-titanium composite oxide relative to the core-shell structure is Wtn, and the weight of the silicon-based material relative to the core-shell structure is Ws, which satisfies the following conditions: 20.0≤Wtn / Ws≤300.

0.

30. A negative electrode, characterized in that Include: The composition according to claim 22.

31. A battery, characterized in that: Include: The negative electrode as claimed in claim 30.

32. A composition, characterized in that Include: A core-shell structure, comprising a core material and a shell material, wherein the shell material is farther away from the center of the core-shell structure than the core material; wherein the core material is selected from at least one of the group consisting of a carbon active material, a structural element mixed oxide and a tin-based alloy; Wherein, the shell material comprises a mixed material, the mixed material comprises a modified silicon material, the modified silicon material comprises a silicon-based material and a polymer, and the polymer comprises a siloxane group; The particle size of the core material at D50 is cD50, and the particle size of the silicon-based material at D50 is sD50, which satisfies the following conditions: 1.0≤cD50 / sD50≤8000.

0.

33. The composition according to claim 32, characterized in that The particle size of the core material at D50 is cD50, and the particle size of the silicon-based material at D50 is sD50, which satisfies the following conditions: 50.0≤cD50 / sD50≤500.0。